Salvadorans in Costa Rica : Displaced Lives - Hayden, Bridget A., 1963- (Book collections on Project MUSE., 2003)
"Salvadorans in Costa Rica: Displaced Lives introduces readers to people from a wide range of class and educational backgrounds who had come to Costa Rica from all over El Salvador. All shared the experience of having become refugees and having settled in a new country under the same circumstances, and when the war in their own country ended, they shared a concern about the issues involved in deciding whether or not to return there. Their diversity allows Hayden to examine the ways in which the language of national identity played out in different contexts and sometimes contradictory ways."--BOOK JACKET.